Optimizing Profitability: The Impact of Cash, Receivables, Inventory, and Working Capital Turnover - Fitriyani, Maya; Hendrawan, Riko (SAN Scientific, 2025)
The aim of the research is to determine the effect of cash turnover, accounts receivable turnover, inventory turnover and working capital turnover on profitability, both partially and simultaneously. The research method used is a quantitative research method and uses secondary data taken from manufacturing companies, especially Food and Beverages, which are listed on the Indonesia Stock Exchange. The research sample selected was 15 companies for the period 2018 to 2022 based on the purposive sampling method. This research analysis method uses panel data regression with a significance level of 5%. The research results show that the variables cash turnover, accounts receivable turnover, inventory turnover and working capital turnover simultaneously influence profitability. Furthermore, partially, cash turnover and inventory turnover do not have a significant effect on profitability; accounts receivable turnover and working capital turnover have a significant effect on profitability. Managerial implications indicate that company management must focus on increasing the efficiency of cash, receivables and inventory turnover, as well as optimizing working capital turnover to increase profitability. Managers need to develop effective strategies for managing cash flow and current assets to maximize company profits.